Is the doctor in? PhD to professional: complementary perspectives in research libraries - Warren, Eleanor (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
Aim: This paper considers how changes in the research landscape are simultaneously changing the skills needs of library staff, and opening up new opportunities for researchers to pursue careers within libraries. It explores what skills, competencies and knowledge staff with doctoral qualifications can bring to library research support services. Context: Librarians working in research support areas need different skills to the skills academic librarians have traditionally needed. There is currently a gap in the training which those undertaking professional librarianship qualifications receive, in relation to the skills needed for research roles. Simultaneously, expansion in the numbers of PhD students in the UK in recent years has been accompanied by the professionalisation of researcher skills development, equipping students with transferable skills for careers outside, as well as inside, academia. Methodology: This paper compares the skills’ needs of research librarians with the competencies and skills of doctoral graduates, specifically in the UK context (as articulated in the Vitae Researcher Development Framework). It also surveys and discusses the skill-set and qualifications of research support staff employed at three UK research libraries. Results: Understanding the needs and, importantly, the behaviours, of researchers is integral to the provision of a successful library research support service. Many of the skills which are necessary for library graduates to have, are those that are already identified as essential researcher skills. The peer-level support offered by library staff with research backgrounds has a role in developing stronger relationships between the library and the academy.